Dietary Supplementation with Green Alga (Chlorella pyrenoidosa) Enhances the Shelf Life of Refrigerated Nile Tilapia (Oreochromis niloticus) Fillets - Leticia Franchin Rodrigues; Mayumi Fernanda Aracati; Susana Luporini de Oliveira; Camila Carlino-Costa; Romário Alves Rodrigues; Mateus Roberto Pereira; Hirasilva Borba; Cleber Fernando Menegasso Mansano; Gabriel Augusto Marques Rossi; Jorge Galindo-Villegas; Gabriel Conde; Luiz Arthur Malta Pereira; et al. (Foods)
Given the critical need for strategies to enhance food safety and quality, particularly due to the rapid spoilage of fish, this study investigated the effect of dietary supplementation with green alga (Chlorella pyrenoidosa) on the shelf life of Nile tilapia (Oreochromis niloticus) fillets. In addition, the microbiological, physicochemical, and sensory qualities of the fillets were evaluated. Eighty-four healthy tilapias (100 ± 2 g) were randomly allocated in three groups (n = 28 per group): a control group (without C. pyrenoidosa supplementation) and two treatment groups supplemented with either 5 or 10 g of C. pyrenoidosa per kg of feed. After 30 days of feeding, the fish were slaughtered and their fillets stored at 4 °C for evaluation at 0, 7, 15, and 30 days post-slaughter (dps). Fillets from fish supplemented with C. pyrenoidosa showed significant lower counts of coliforms, Enterobacteriaceae, and mesophilic and psychrotrophic microorganisms compared to the control. Supplementation also reduced thiobarbituric acid reactive substance (TBARS) levels and pH over the 30-day storage period. Sensory and color analyses indicated improved brightness, appearance, and firmness in fillets from treated groups, while control fillets exhibited poorer odor quality. Our findings demonstrate a dose-dependent effect of C. pyrenoidosa supplementation in improving the microbiological, physicochemical, and sensory quality of Nile tilapia fillets during refrigerated storage for up to 30 days.